Disproportionality analysis of drug-associated progressive multifocal leukoencephalopathy: roles of underlying diseases and immunomodulatory therapies in FAERS - Lin, Xiaozhen; Qin, Naishen; He, Baoxia; Chen, Jinhua; Zhang, Yajuan; Wang, Hui; Liu, Weiling (Frontiers in Immunology, 2026)
BackgroundProgressive multifocal leukoencephalopathy (PML), a rare and often fatal JC virus–mediated disease, is a significant concern in immunocompromised patients.ObjectiveFollowing READUS-PV guidelines, this study evaluated disproportionality signals for PML associated with specific drugs and underlying diseases using the FDA Adverse Event Reporting System (FAERS).MethodsWe identified PML cases in FAERS (2004 Q1–2024 Q4) and excluded those associated with HIV/AIDS. For drugs with ≥3 PML reports, disproportionality was assessed using the reporting odds ratio (ROR) and proportional reporting ratio (PRR), reported with 95% confidence intervals and χ² statistics, respectively. Subgroup analyses were conducted by age, sex, reporting region, and patient outcome. We also characterized the spectrum of underlying diseases and time to onset (TTO).ResultsWe analyzed 6,864 PML reports; in a sensitivity analysis excluding cases with TTO ≤60 days, 6,258 reports remained. Fifty-four drugs showed significant signals in primary analysis with the exception of acalabrutinib in the analysis restricted to 6,258 cases, including established high-risk agents and potential novel associations. Notably, we observed signals with four monoclonal antibodies (daratumumab, elotuzumab, epcoritamab, and isatuximab); isatuximab had no previous mentions in regulatory labels or published literature to our knowledge. Among established agents, natalizumab had the highest number of reports (n=1,848; ROR 40.7), and rituximab also showed a strong signal (n=1,296; ROR 41.8). PML was most frequently reported in multiple sclerosis (32.28%) and B-cell non-Hodgkin lymphomas (9.44%). TTO varied by agent; natalizumab showed the longest median TTO (44.0 months; 95% CI: 41.8–46.7). Median TTO for antineoplastic drugs (13.6 months; 95% CI: 11.5–15.9) was significantly shorter than for non-antineoplastic drugs (42.4 months; 95% CI: 39.7–44.1).ConclusionsThese findings reinforce established and emerging PML reporting signals with immunomodulatory therapies and support heightened pharmacovigilance—particularly for novel monoclonal antibodies used in hematologic malignancies.